Mathematical model for knowledge testing - Krylovas, Aleksandras; Kosareva, Natalja (Lietuvos matematikos rinkinys, 2008)
There is a mathematical model for obtaining test responses probability distribution proposed. This enables to formulate recomendations for selection of test items for different groups of tested population according to their attainment level.